A Charge-Sharing based 8T SRAM In-Memory Computing for Edge DNN Acceleration - Lee, Kyeongho; Cheon, Sungsoo; Jo, Joongho; Choi, Woong; Park, Jongsun (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
This paper presents a charge-sharing based customized 8T SRAM in-memory computing (IMC) architecture. In the proposed IMC approach, the multiply-accumulate (MAC) operation of multi-bit activations and weights is supported using the charge sharing between bit-line (BL) parasitic capacitances. The area-efficient customized 8T SRAM macro can achieve robust and voltage-scalable MAC operations due to the charge-domain computation. We also propose a split capacitor structure-based 5/6-bit reconfigurable successive approximation register analog-to-digital converter (SAR-ADC) to reduce the hardware cost of an analog readout circuit while supporting higher precision MAC operations. The proposed reconfigurable SAR-ADC has been exploited to implement layer-by-layer mixed bit-precisions in convolution layer for increasing energy efficiency with negligible accuracy loss. The 256×64 8T SRAM IMC macro has been implemented using 28nm CMOS process technology. The proposed SRAM macro achieves 11. 20-TOPS/W with a maximum clock frequency of 125MHz at 1. 0V. It also supports supply voltage scaling from 0.5V to 1.1V with the energy efficiency ranging from 8.3-TOPS/W to 35.4-TOPS/W within 1 % accuracy loss.